Seismic performance of emergency diesel generator for high frequency motions - Young-Soo Jeong; Eun-Rim Baek; Bub-Gyu Jeon; Sung-Jin Chang; Dong-Uk Park (Nuclear Engineering and Technology, 2019)
The nuclear power plants in South Korea have been designed in accordance with the U.S. Regulatory Guide 1.60 (R.G 1.60) design spectrum of which the peak frequency range is 2–10 Hz. The characteristics of the earthquakes at the Korea nuclear power plant sites were observed to be closer to that of Central and Eastern United States (CEUS) than the R.G 1.60, which is a lower amplification in a low frequency range, and a higher amplification in a high frequency range. The possibility of failure for sensitive power plant components in the high frequency range has been considered and evaluated. In this study, in order to improve the reliability of nuclear plant and administrative control procedures, seismic tests of an emergency diesel generator (EDG) were conducted using a shaking table under both high and low frequency ranges. From the tests, oil/lubricant leaks from the bolt connections, the fuel filter and the fuel inlet were observed. Therefore, the check list of nuclear plant components after an earthquake should include bolt connections of EDG as well as anchor bolts. Keywords: Emergency diesel generator, Seismic performance, High frequency motion, Shaking table test